2017
DOI: 10.1007/s10237-017-0895-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and frequency distributions of regional deformation in the healthy human lung

Abstract: Understanding regional deformation in the lung has long attracted the medical community, as parenchymal deformation plays a key role in respiratory physiology. Recent advances in image registration make it possible to noninvasively study regional deformation, showing that volumetric deformation in healthy lungs follows complex spatial patterns not necessarily shared by all subjects, and that deformation can be highly anisotropic. In this work, we systematically study the regional deformation in the lungs of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 32 publications
1
44
0
6
Order By: Relevance
“…The image-based biomechanical analysis was performed as previously described 5 6. Basically, tetrahedral finite element meshes were used in the segmented masks of the lungs (left and right), the meshing process was carried out via the usage of the Computational Geometry Algorithms Library 22.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The image-based biomechanical analysis was performed as previously described 5 6. Basically, tetrahedral finite element meshes were used in the segmented masks of the lungs (left and right), the meshing process was carried out via the usage of the Computational Geometry Algorithms Library 22.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, three-dimensional (3D) biomechanical analysis based on finite-element techniques has been introduced to quantify regional lung strain from CT images 5 6. Using this method, our group quantified regional strain in 11 human healthy subjects during a single full inspiration (total lung capacity) in supine decubitus, finding a significant effect of gravity on volumetric regional deformation 6.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a continuum-mechanics perspective, the optimal transformation u obtained from the solution of the DIR problem can be considered as a displacement field, from which a strain tensor field can be computed using the gradient of the displacement field ∇u. The study of not only motion but also deformation at a regional level in the lung has revealed that deformation in the lung tissue can be highly heterogenous and anisotropic [3,25], thus providing new deformation-based markers to understand lung physiology [13], showcasing the potential of DIR strain analysis as a tool in the detection and diagnosis of pulmonary disease. These advances notwithstanding, it has been recently shown that state-of-the-art strain analysis techniques based on direct differentiation of DIR solutions can be highly inaccurate as they are very sensitive to noise, discretization level and embedded anatomical boundaries [26].…”
Section: Introductionmentioning
confidence: 99%